Long-term monitoring of zinc corrosion behavior in typical hot and dry atmosphere environment in Turpan, China. Issue 5 (14th August 2018) - Kang, Chunhui; Kong, Decheng; Yao, JiZheng; Guo, Chunyun; Wang, Li; Xiao, K.; Dong, C.F.
Abstract : Purpose: This paper aims to investigate the corrosion behavior of zinc in a typical hot and dry atmosphere. It proposes the dynamic corrosion for different exposure periods. Results can provide the basic data and corrosion mechanism of zinc in such environment. Design/methodology/approach: In this paper, the authors investigated the corrosion behavior of pure zinc exposed in the typical hot and dry environment in Turpan for one-four years, which has never been studied. Scanning electron microscopy, laser scanning confocal microscopy, electron probe micro-analyzer (EPMA), X-ray photoelectron spectroscopy (XPS) and X-ray diffraction (XRD) were conducted to measure the corrosion morphology and products of zinc. Finally, combining electrochemical impedance spectroscopy and scanning Kelvin probe techniques, the corrosion mechanism of zinc in Turpan was examined. Findings: The thickness loss of the zinc followed an exponential law with respect to exposure time: D = 3.17 t 0.61, and both of the rust layer resistance and the charge transfer resistance increased with exposure time. The corrosion products mainly comprised ZnO, Zn(OH)2, Zn5 (CO3 )2 (OH)6, Zn4 SO4 (OH)6 ·5H2 O and Zn12 (SO4 )3 Cl3 (OH)15 ·5H2 O. The Kelvin potentials shifted toward the positive direction from −0.380 to −0.262 V (vs saturated calomel electrode [SCE]) when the exposure time extended from one to four years and the distribution of the corrosion products became more and more uniform. Originality/value: The corrosion behavior of pure zinc in the typical hot and dry environment in Turpan has not been studied. The dynamic corrosion for different exposure periods was obtained. The corrosion products were systemically investigated via energy-dispersive X-ray spectroscopy, EPMA, XPS and XRD.